2020
DOI: 10.1159/000508794
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Width and Implantable Pulse Generator Longevity in Pallidal Deep Brain Stimulation for Dystonia: A Population-Based Comparative Effectiveness Study

Abstract: Introduction: A wide range of pulse widths (PWs) has been used in globus pallidus internus (GPi) deep brain stimulation (DBS) for dystonia. However, no specific PW has demonstrated clinical superiority, and the paradigm may differ among DBS centers. Objective: To investigate how different paradigms of PWs in GPi DBS for dystonia affect implantable pulse generator (IPG) longevities and energy consumption. Methods: Thirty-nine patients with dystonia treated with bilateral GPi DBS at 2 Swedish DBS centers from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Although there is no absolute consensus regarding the optimal stimulation parameters for dystonia DBS, some general points can be made. Longer pulse widths above 60 ms, often employed, are no more effective than shorter pulse widths and may induced more side effects and battery drain [73][74][75]. Typically, high-frequency stimulation of 130 Hz is used but lower frequencies of 60 Hz can be of similar efficacy with potentially fewer side effects [76].…”
Section: Deep Brain Stimulation Stimulation Parameters and Technologymentioning
confidence: 99%
“…Although there is no absolute consensus regarding the optimal stimulation parameters for dystonia DBS, some general points can be made. Longer pulse widths above 60 ms, often employed, are no more effective than shorter pulse widths and may induced more side effects and battery drain [73][74][75]. Typically, high-frequency stimulation of 130 Hz is used but lower frequencies of 60 Hz can be of similar efficacy with potentially fewer side effects [76].…”
Section: Deep Brain Stimulation Stimulation Parameters and Technologymentioning
confidence: 99%
“…Chronic stimulation in the most posteroventral portion of GPi is most effective (23). Dystonia DBS typically requires higher electrical parameters than STN DBS for Parkinson's disease, however longer stimulation pulse widths above 60 ms are not beneficial and are less energy efficient (24)(25)(26), while lower frequency stimulation below 100 Hz may be useful in selected patients (27). Rare treatment failures after GPi DBS may occur in all categories of dystonia including genetic isolated generalized dystonia and appear independent of technical reasons such poor lead placement (28).…”
Section: Overview Of Gpi Dbs In Dystoniamentioning
confidence: 99%
“…On the other hand, Lumsden et al acknowledged that no difference in battery life was observed between Soletra® and Kinetra® IPGs [14]. Fakhar et al and Ågren et al showed that battery life is not different in different models [35,36]; thus, it can be concluded that the life of embedded batteries in addition to differ- ent models also depends on different diseases because the settings of the DBS device are different for different patients. For example, depending on the type of malfunction, the lower the set frequency of the device, the longer the battery life is to 48 months [26,37,38], which can be seen in different statistical populations of studies.…”
Section: Battery Life Associated With a Variety Of Ipg Modelsmentioning
confidence: 99%